Design and Simulation of a 12-Pulse D-STATCOM for Voltage Sag Mitigation and Power Quality Improvement in Unbalanced Distribution Systems - Masdi, Hendri; Bin Abdul Wahab , Noor Izzri; Husin, Muhammad; Hasanah, Rini Nur (Faculty of Engineering, Universitas Brawijaya, 2025)
The research introduces a 12-pulse D-STATCOM model developed and simulated to address voltage sag mitigation and power quality enhancement in unbalanced distribution feeders. It tackles critical power quality problems such as voltage depressions, harmonic disturbances, and declining power factor, all of which negatively influence system reliability and efficiency. The 12-pulse arrangement was realized by integrating two 6-pulse Voltage Source Converters (VSCs) through a phase-shifted transformer, which enabled the suppression of dominant low-order harmonics. The overall system was constructed and analyzed in MATLAB/Simulink, where an SRF-based control method was employed to ensure precise reactive power support and rapid voltage restoration. The simulation outcomes indicate notable performance gains: THD decreased from 8.5% in the conventional 6-pulse unit to 3.2%, the power factor increased from 0.85 to 0.98, and the network voltage recovered within approximately 0.02 seconds following a 30% voltage dip. These findings demonstrated that the 12-pulse D-STATCOM provided superior harmonic mitigation, faster dynamic response, and improved system stability compared to the conventional 6-pulse design. The novelty of this study lies in proving that the 12-pulse configuration offers a technically practical yet practically feasible alternative, making it highly relevant for real-world power distribution applications.